Pandemic Fatigue in Nursing Undergraduates: Role of Individual Resilience and Coping Styles in Health Promotion - Kumar, Rajesh; Beniwal, Kalpana; Bahurupi, Yogesh (Frontiers in Psychology, 2022)
Introduction: The COVID-19 pandemic was soon declared a global health threat and had significant economic and health implications. Unprecedented government measures brought massive shifts in teaching-learning pedagogy in nursing to curb the infection. The study was conducted to explore the predictors of pandemic fatigue among nursing undergraduates and mediating role of individual resilience and coping styles during the third wave in India. Methods: This online survey included 256 undergraduate nursing students studying at Tertiary Care Teaching Hospital in North India. Lockdown/Pandemic Fatigue Questionnaire, Brief Resilience Scale, and Coping Behaviour Questionnaire were used to collect the information. Appropriate descriptive and inferential statistics were applied to compute the results. Results: Nursing undergraduates reported a moderate level of fatigue during the restrictions imposed at the time of the third wave. Students’ year of study (p=0.001), tested positive during pandemic (p=0.003) and post-covid-19 hospitalization (p=0.026) found associated with higher fatigue status. Advanced age (p=0.046), and higher personal resilience status (p<0.001) were associated with lower fatigue levels. Resilience status (ß = - 4.311, p<0.001) and second year of study (ß=3.198, p=0.015) reported an independent predictor of pandemic fatigue in students. Conclusions: Findings suggest that lockdown-related fatigue was common in nursing undergraduates. Considering negative consequences on mental health, routine psychosocial screening of the nursing students should be conducted. Recommending stress-relieving measures should be enforced to help nursing undergraduates to combat lockdown-induced exhaustion.